2020
DOI: 10.3390/ijerph17238995
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and Road Accidents Involving Pedestrians as Unprotected Road Users

Abstract: According to the World Health Organization (WHO), more than half of all road fatalities involve vulnerable road users, i.e., pedestrians, cyclists, and motorcyclists. Poland is classified as one of the European Union (EU) countries marked by low road safety, with a higher frequency of accidents involving pedestrians compared to other EU countries (31% of all fatalities). Among unprotected road users, a significant group of victims are pedestrians, who are often under the influence of alcohol. This study aims t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…It is noteworthy that men are more likely to die from road accidents [ 26 ]. Our own study showed that despite favorable trends in both groups, mortality rates in the male group were almost four times higher than in the female group, both at baseline and in the final year of the analysis and this trend applied equally to raw and standardized rates.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that men are more likely to die from road accidents [ 26 ]. Our own study showed that despite favorable trends in both groups, mortality rates in the male group were almost four times higher than in the female group, both at baseline and in the final year of the analysis and this trend applied equally to raw and standardized rates.…”
Section: Discussionmentioning
confidence: 99%
“…e results showed that older pedestrians suffered more serious pedestrian injuries; trucks and vans were more likely to cause serious pedestrian injuries [18]. While researching the influence of alcohol, Lasota's survey found that younger victims were more likely to die at the scene of an accident, especially in rural areas [19].…”
Section: Introductionmentioning
confidence: 99%
“…The harmful use of alcohol can also result in harm to others, such as family members, friends, co-workers and strangers (Dale et al, 2010;Greenfield, 2015;Laslett, 2013;Sharma et al, 2016). Among the most dramatic manifestations of harm to persons other than drinkers are road traffic injuries (Lasota et al, 2020;Nasueb, 2022;Stewart et al, 2012) and consequences of prenatal alcohol exposure that may result in the development of fetal alcohol spectrum disorders (FASD) (Kaminen-Ahola, 2020; Mattson et al, 2019;Popova et al, 2023;Wozniak et al, 2019). "The harms to others may be very tangible, specific and time-bound (e.g.…”
Section: Introductionmentioning
confidence: 99%